Principal Academic Supervision Facilitates Deep Learning In Inclusive Elementary Classrooms: Supervisi Akademik Kepala Sekolah Memfasilitasi Pembelajaran Mendalam Di Sekolah Dasar Inklusif - Setiati Pai; Hermanto Hermanto (Academia Open, 2026)
General Background The shift toward twenty-first-century competencies requires educators to facilitate meaningful, mindful, and joyful educational experiences. Specific Background Implementing these pedagogical strategies presents complex challenges in integrated environments where educators must accommodate diverse cognitive profiles and special educational needs. Knowledge Gap Current professional development often prioritizes administrative document reviews over the continuous, collaborative coaching required to help educators design authentic, student-centered classroom activities. Aims This research investigates how structured leadership interventions facilitate the pedagogical transition toward rigorous conceptual instruction in an integrated primary school setting. Results Through two collaborative action cycles, educators' pedagogical comprehension progressed from a 51% baseline to 83%. Correspondingly, student conceptual mastery and engagement metrics grew from 44% to 79%, reflecting positive shifts in inclusive classroom management and differentiated instruction. Novelty This study uniquely links cyclical, reflective leadership mentoring directly with both educator competency metrics and the cognitive advancement of special needs learners. Implications Deploying systematic, non-evaluative observation and feedback frameworks provides school leaders with a proven mechanism to transform teaching quality and cultivate highly adaptive, learner-centric environments. Highlights Structured leadership mentoring progressed teacher pedagogical comprehension from a 51% baseline to 83% across two cycles. Learner conceptual mastery and classroom engagement metrics grew significantly from 44% to 79%. Continuous reflective dialogue successfully transitioned teachers toward utilizing differentiated instructional strategies and varied learning media. Keywords Academic Supervision; Deep Learning; Inclusive Education; Teacher Competence; Action Research